Acute toxicity, sublethal effect and changes in the behavior of Lasioderma serricorne Fabricius (Coleoptera: Anobiidae) exposed to major components of essential oils (Research, Society and Development, 2020)
The objective of this work was to evaluate the acute toxicity, sublethal effect and behavioral alteration of L. serricorne exposed to the major components of essential oils, thymol, camphor, terpineol, camphene, eucalyptol, limonene, βpinene and eugenol. The adults of L. serricorne , aged 5 days, not sexed, were submitted to acute toxicity by fumigation, used fumigation chambers, 200 ml glass containers with 20 insects, subsequently the sublethal effect, longevity and behavioral response. The results show that the major components and mixtures caused acute toxicity, reduced the survival time and production of offspring and altered the behavioral activity of L. serricorne. The major components eucalyptol and terpineol presented 65% mortality, in which the mixtures terpineol + eucalyptol and camphor + thymol presented 47 and 52% over adults of L. serricorne. The mixture between terpineol + limonene allowed only 4% ofadults to L. serricorneemerge. Behavioral activity was altered by the eucalyptol + eugenol mixture. The results showed that the major components and mixtures are promising for the preparation and production of new insecticides.